The Urgency for Peace in Teachings of John Paul II - Jerzy Lewandowski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Peace has always been a topic of great importance. Its presence is desired by all nations and societies. It brings the world together in unity. John Paul II considered peace to be an integral part in creation of an independent and healthy society. Papal encyclicals and messages, intended to present the response of the teaching Church to problems that arise from time to time, often dwell on the principles that advocate peace. Since freedom and peace are in many cases a privilege for many nations, the mentioned pope commits himself to speak about the cruelty and evilness of wars and national conflicts. Pope John Paul II denounces intolerance as denial of freedom for many people, and consequently a great threat to peace. The pope teaches that peace has its roots in the family. Yet, in many societies, the family is deprived of the utmost importance that it certainly deserves. Without the adequate means for a decent livelihood, families can experience hardship in committing themselves to promote solidarity and a proper social fabric worthy of human dignity. For John Paul II, a nation’s freedom and peace are safeguarded and promoted through particular attention and a much-devoted effort by strong and healthy families.